SMA-based simulation data demand acquisition in the field of mechanical equipment. (November 2020) - Jingwei, Wang; Ping, Gu; Siyu, Li; Jian, He
Abstract: In view of the complexity of the simulation system in the field of mechanical equipment and the difficulty in obtaining the simulation data, the idea of requirement engineering is adopted. After comparing the current common demand analysis methods, the comprehensive micro analysis method is introduced to analyze the data demand. In this paper, the application process model of the comprehensive micro analysis method is also constructed to describe the application process of the method.